As potencialidades da feira agroecológica Arpa-Sul Pelotas: produção, comercialização e certificação - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This study aims to reflect on the consumption of healthy food through organic foods sold at the ecological fair in Pelotas. It is understood that ecological fairs are more than a point of commerce, in reality they are distribution channels versus contacts of sources of certified organic products. It uses a bibliographic, documental study, with a qualitative approach, of the descriptive-exploratory type, where interviews were carried out with the stallholders, demonstrating the potential of the ecological fair, understanding that they are beyond the dissemination of a healthy food culture. The expectations of this study refer to contributing to the dissemination of the work of the market Ecologic de Pelotas, with the dissemination of a healthy food culture, since the production of organic products primarily benefits the earth, extends to the consumer and by generating trust relationships between producer and consumer that spans many years.It is believed that this work will contribute to new propositions with the organic food sector and, furthermore, a broaderreflection can be inferred regarding the need for new, more sustainable consumption patterns. In this way, it will be possible to approximate the real needs, from the understanding of what they most value when buying organic products, whether in terms of concrete attributes (price, appearance of the products), abstract (taste, quality) and also, psychological factors (feeling safety when eating.
Keywords: Feira Ecológica ARPA-SUL; Agroecologia; Alimentação saudável; ARPA-SUL Ecological Fair; Agroecology; Healthy eating; CNPQ::CIENCIAS SOCIAIS APLICADAS